PERAN UNITED NATIONS INTERNATIONAL CHILDREN’S FUND (UNICEF) DALAM MENANGGULANGI PENGGUNAAN TENTARA ANAK PADA KONFLIK ISIS DI SURIAH TAHUN 2015-2018 - Suranta, Ad; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The international organization, namely the United Nations Children's Fund (UNICEF), has been authorized by international humanitarian law and must be placed in 193 countries and focuses on child protection issues. UNICEF plays an important role in addressing the use in armed conflict such as child soldiers in the ISIS conflict in Syria. The Islamic State of Iraq and Syria (ISIS) is a radical movement that emerged as a result of the political, economic and socio-cultural situation in the Middle East. This research aims to determine UNICEF's role in overcoming the use of child soldiers in the ISIS conflict in Syria through the Not a Lost Generation (NLG) program, as a program to save child soldiers and protect children in the ISIS conflict in Syria. The methodology for writing this paper uses a qualitative type and descriptive method and the data obtained for this paper comes from library research using trusted sources in the form of journals, books, official reports and websites. This research adopts the theory of the role of international organizations as explained by Clive Archer, in line with the aim of analyzing the role of international organizations or the role of UNICEF. This research found that in 2015-2018, UNICEF also played roles such as UNICEF as an instrument, UNICEF as an arena, and UNICEF as an independent actor. UNICEF created this NLG program as a result of careful preparation between UNICEF in collaboration with the government, NGOs and individuals. Keywords: UNICEF, ISIS, No Lost Generation, Child Soldiers